Studi Dinamika Kelompok Peternak Sapi Perah di Kabupaten Banyumas - Kartika, Maulidina Wahyu; Sugiarto, Moch; Nuskhi, Muhammad (ANGON: Journal of Animal Science and Technology, 2021)
Background. This research aims to find out dynamics group of dairy cow farmer and characteristics of dairy cow farmer, to find out the corelation between dynamics group and characteristics of dairy cow farmer. Materials and methods. The research method used is survey. The subject of this research is dairy cow farmer taken from one of area that has dairy farming using sampling purposive technique. The collecting sample of respondence uses slovin's formula. It is obtained fourty five dairy cow farmers then applies proportional random sampling to each subpopulation. Futhermore, this research is put on descriptive analysis and spearman Rank Corelation. Results. The result of this result shows that dynamics group of dairy cow farmer in Banyumas is 82.22% in dynamics condition, age of dairy cow farmer is productive (66.67%), elementary level of dairy cow farmer is 60%, experience category more than 10 years of farming is 51.11%. Conclusion. There is no relationship between farmers characteristic and group dynamics (P>0.05). It can be concluded that has no corelation between education and dynamic group (P<0.05). Moreover, It has no corelation also between experience farming and dynamics group (P>0.05).